2009
DOI: 10.1007/s10211-009-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Do ecotypes of bushbuck differ in grouping patterns?

Abstract: Grouping patterns within the genus Tragelaphus suggest that species inhabiting open areas tend to live in larger groups, while species preferring dense habitats live solitarily or in small family groups. We asked if similar variation would be concealed in the within-species variation of bushbuck (Tragelaphus scriptus). Recent molecular phylogeographic analyses revealed several locally adapted forms of bushbuck in different ecoregions on the African continent. We compared group sizes of south-eastern bushbuck (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Based on the result, the aggregation of group of bushbuck population in the dry season in a limited area and splitting into smaller groups and dispersal to a wider area may be due to their selective feeding behavior to get more preferable forage and they are mostly solitary. This supports the findings of Wronski et al (2009), which observed that bushbucks are indeed a solitary species, as one individual peer group was the most frequent group size in both adults and sub adult groups in all populations they examined. During the wet season, the solar radiation is reduced by the cloud cover; hence, the animals leave dense forest and congregate in the open for feeding.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the result, the aggregation of group of bushbuck population in the dry season in a limited area and splitting into smaller groups and dispersal to a wider area may be due to their selective feeding behavior to get more preferable forage and they are mostly solitary. This supports the findings of Wronski et al (2009), which observed that bushbucks are indeed a solitary species, as one individual peer group was the most frequent group size in both adults and sub adult groups in all populations they examined. During the wet season, the solar radiation is reduced by the cloud cover; hence, the animals leave dense forest and congregate in the open for feeding.…”
Section: Discussionsupporting
confidence: 90%
“…Our study shows that among our ruminant sample, deer species and some bovid species such as the blue duiker (P. monticola), addax (Addax nasomaculatus) and most of tragelaphine antelopes (Tragelaphus imberbis, T. scriptus, T. spekii, T. strepsiceros), display a relatively long growth period (relative to their size). These species, except for addax and the insular Svalbard reindeer, dwell in wooded and closed habitats, which are environments characterized by lower predation pressure than open habitats (Clutton-Brock et al, 1982;Köhler, 1993;Owen-Smith, 1993;Wronski et al, 2009). Addax dwells in desert, habitat characterized by resource limitation and scarcity of predators (Mallon and Kingswood, 2001 also characterize the habitat of the arctic reindeer from Svalbard archipelago (Aanes et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…This is not appropriate in studies of group size distribution because that would mean excluding a large proportion (often the majority) of observed individuals, thus greatly falsifying the results. Similar rightskewed frequency distributions characterise herds of many ungulate species (Sinclair 1977;Clutton-Brock 1982;Gueron 1995;Wronski et al 2009;Ramesh et al 2011;Dar et al 2012;Buuveibaatar 2013;Brennan et al 2015;Djaković et al 2015;Semeñiuk 2015), including the subject of our present paper, the Rocky Mountain mule deer (Odocoileus hemiounus hemionus) (Bowyer 2001;Lingle 2003;Mejía Salazar et al 2016).…”
mentioning
confidence: 60%